The politics of taste : Beatriz González and Cold War aesthetics - Reyes, Ana María (College teacher) (Art history publication initiative., 2019)
In The Politics of Taste Ana María Reyes examines the works of Colombian artist Beatriz González and Argentine-born art critic, Marta Traba, who championed González's art during Colombia's National Front coalition government (1958-74). During this critical period in Latin American art, artistic practice, art criticism, and institutional objectives came into strenuous yet productive tension. While González's triumphant debut excited critics who wanted to cast Colombian art as modern, sophisticated, and universal, her turn to urban lowbrow culture proved deeply unsettling. Traba praised González's cursi (tacky) recycling aesthetic as daringly subversive and her strategic localism as resistant to U.S. cultural imperialism. Reyes reads González's and Traba's complex visual and textual production and their intertwined careers against Cold War modernization programs that were deeply embedded in the elite's fear of the masses and designed to avert Cuban-inspired revolution. In so doing, Reyes provides fresh insights into Colombia's social anxieties and frustrations while highlighting how interrogations of taste became vital expressions of the growing discontent with the Colombian state.